Direct and Oblique Translation Methods in the Subtitle of Atlas Movie - Agung, Malla Kharima; Purnamasari, Yessy (Journal of English Teaching, Literature, and Applied Linguistics, 2026)
This study focuses on analyzing the direct and oblique translation methods in the Indonesian subtitles of the Atlas movie. The data for this study is based on Act II of the Atlas movie’s structure, the confrontation section of the movie that consists of 486 data. The data was analysed using Vinay & Darbelnet's theory about translation methods. Additionally, Catford's theory about transposition functions as a supported theory of the transposition procedure in this study. The objectives of this study are to identify the translation methods used in the Indonesian subtitles of the Atlas movie and to identify the dominant methods in the Indonesian subtitles of the movie. The research method used is a qualitative method. The result of this study reveals the use of the direct and oblique translation method with the literal procedure of 26.1%, the borrowing procedure of 7.2%, the calque procedure of 3.7%, the transposition procedure of 24.7%, the modulation procedure of 24.5%, the equivalence procedure of 13.4%, and the adaptation procedure of 0.4% Based on the result, the dominant translation method is oblique translation method with 63% This reflects the importance of mastering both SL and TL to make the SL message clear and appropriately conveyed to the TL audience. The movie’s sci-fi genre with complex terms further supports the method’s dominance.